Ultrastructure of the dorsal claustrum in cat. I. Types of neurons. Issue 1 (1st January 2019) - Hinova-Palova, Dimka; Iliev, Alexandar; Landzhov, Boycho; Kotov, Georgi; Stanchev, Stancho; Georgiev, Georgi P.; Kirkov, Vidin; Edelstein, Lawrence; Paloff, Adrian
ABSTRACT: Background : The claustrum is the most densely connected brain structure by volume and has extensive reciprocal connections with numerous cortical areas. It is divided into two embryologically distinct parts – dorsal and ventral claustrum. Despite numerous recent findings, much remains unknown about its structure and function. Objective : The aim of our study was to observe and describe the ultrastructural characteristics of the different types of neurons in the dorsal claustrum of the cat and to discuss their possible functional significance. Design : We used a total of 10 healthy young male cats. The obtained histological material was processed in the usual way for transmission electron microscopy. Results : We observed four types of neurons in the dorsal claustrum of cats – large, medium-sized, small and 'dwarf' cells. While large and medium-sized neurons had a large electron-lucent nucleus with a wide cytoplasmic ring and an abundance of cellular organelles, small neurons had electron-lucent nuclei with varying degrees of dispersed and condensed chromatin and were poor in organelles. 'Dwarf' cells had the typical appearance of neurogliaform cells. Conclusion : Based on their ultrastructural features, we recognized large and medium-sized neurons as efferent, or projection neurons. On the other hand, small neurons and neurogliaform 'dwarf' cells had the typical ultrastructure of inhibitory interneurons.